Respuesta :

Answer:

(7x−5)(3x+4)

Step-by-step explanation:

I think this is the answer

Answer:

(7x−5)(3x+4)

Step-by-step explanation:

Step-1 : Multiply the coefficient of the first term by the constant   -21 • 20 = -420

Step-2 : Find two factors of  -420  whose sum equals the coefficient of the middle term, which is   13 .

     -420    +    1    =    -419

     -210    +    2    =    -208

     -140    +    3    =    -137

     -105    +    4    =    -101

     -84    +    5    =    -79

     -70    +    6    =    -64

     -60    +    7    =    -53

     -42    +    10    =    -32

     -35    +    12    =    -23

     -30    +    14    =    -16

     -28    +    15    =    -13

     -21    +    20    =    -1

     -20    +    21    =    1

     -15    +    28    =    13    That's it

Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above,  -15  and  28

                    -21x2 - 15x + 28x + 20

Step-4 : Add up the first 2 terms, pulling out like factors :

                   -3x • (7x+5)

             Add up the last 2 terms, pulling out common factors :

                   4 • (7x+5)

Step-5 : Add up the four terms of step 4 :

                   (-3x+4)  •  (7x+5)

ACCESS MORE